2021
DOI: 10.1007/s00787-021-01728-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and use of health care services in opioid-exposed school-aged children compared to foster children

Abstract: Given the concerns raised regarding the effects of prenatal exposure to methadone and buprenorphine on the developmental outcomes of the children, this study assessed mental health and use of services in a national sample of school-aged children (N = 78) born to women enrolled in opioid maintenance treatment during pregnancy, compared with a group of foster children (N = 140). The majority of the opioid-exposed children lived with their birth parent(s) at the time of assessment (N = 62), while 16 lived in fost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Behavioral problems were assessed in 14 studies in this age group ( 30 , 37 , 38 , 40 , 47 , 57 , 71 , 72 , 76 , 78 , 85 , 87 , 96 , 98 ). The most common instrument ( n = 6) used to assess behavior was the Child Behavior Checklist (CBCL) in middle childhood.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral problems were assessed in 14 studies in this age group ( 30 , 37 , 38 , 40 , 47 , 57 , 71 , 72 , 76 , 78 , 85 , 87 , 96 , 98 ). The most common instrument ( n = 6) used to assess behavior was the Child Behavior Checklist (CBCL) in middle childhood.…”
Section: Resultsmentioning
confidence: 99%
“…Previous publications from this study group have addressed various aspects of both parental and child functioning (17,35,(38)(39)(40) throughout the 8-year follow-up-period. Here we analyze key outcomes across the whole study period, focusing primarily on parenting stress and child behavioral problems.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, studies on OMT cohorts in this country have shown very little concomitant drug use in pregnancy and birth parameters of children born to mothers in OMT are within the normal ranges (15,16). A substantial number of mothers retain custody 8 years after delivery and a recent study showed that children growing up with parents in stable OMT have significantly better mental health in early school age than other vulnerable groups such as children placed in foster care (17).…”
mentioning
confidence: 99%
“… 11 Opioid exposure during the prenatal and infancy periods might be an emerging risk factor for neuropsychiatric outcomes. While previous studies reported that exposure to opioids during the prenatal period is associated with neuropsychiatric disorders, such as attention deficit hyperactivity disorder, alcohol misuse, and depression, 12 13 others suggest that exposure to opioids during pregnancy may not be deleterious to early childhood neurobehavioural development. 14 15 Given the potential confounding factors and limited cohort size in earlier research, 16 a more precise investigation with a large scale birth cohort is warranted.…”
Section: Introductionmentioning
confidence: 99%